The Implementation of Environmental Communication for Community Waste Management Initiative in Bontang, East Kalimantan - Kadek Dristiana Dwivayani; Restu Almalita (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
Improper waste management has a detrimental effect on the quality of life due to its impact on the ecosystem and public health. Therefore, effective environmental communication is required to raise public awareness about preserving the environment. This research examines the role of environmental communication implemented by Mekarsari Guntung Sejahtera Cooperative in the Guntung community of Bontang City. The study utilizes a descriptive qualitative method focusing on the function of environmental communication. The findings indicate that Mekarsari Cooperative employs two communication functions: constitutive and pragmatic. In the constitutive function, environmental communication promotes values of awareness, compassion, and cooperation to create a clean environment and economically empowered community. In the pragmatic function, environmental communication is used to educate and inform individuals about proper waste management methods and their benefits for the community.